Papel da regiao AV3V no choque septico experimental em ratos tratados com NaCl 7,5% - Fracasso, J. F. [UNESP]; Souza, Ricardo Luiz Nunes de [UNESP] (My University, 1996)
The effect of intravenous infusion of hypertonic saline (HS) on the recovery of mean arterial pressure (MAP) during septic shock was studied in sham-operated rats and in rats with electrolytic lesion in the anteroventral third ventricle (AV3V) region. Our results show that intravenous HS infusion in rats treated with endotoxin (Etx) partially restores MAP, but when we have a severe shock produced by Etx, HS was not able to reverse the hypotension. We also show that the integrity of the AV3V region is essential for the protective action of HS in endotoxin shock. It is possible that NO production contributes to the deleterious effect of endotoxin. So, the unraveling of the release of NO by the vascular endothelium and their role as regulators of vascular tone is increasing our understanding of the physiology and pathophysiology of the cardiovascular system and will therefore enhance the possibilities of preventing and treating endotoxin shock.
The role of AV3V region in experimental septic shock in rats treated with NaCl 7,5%
Keywords: 7,5% NaCl; AV3V lesion and septic shock; endotoxin; hypertonic saline; nitric oxide; sodium chloride; animal experiment; animal model; blood pressure; blood vessel tone; brain region; brain ventricle; intracerebroventricular drug administration; nonhuman; rat; septic shock